Development of empirical models for performance evaluation of UASB reactors treating poultry manure wastewater under different operational conditions - Yetilmezsoy, Kaan; Sakar, Suleyman (ELSEVIER, 2008)
A nonlinear modeling study was carried out to evaluate the performance of UASB reactors treating poultry manure wastewater under different organic and hydraulic loading conditions. Two identical pilot scale up-flow anaerobic sludge blanket (UASB) reactors (15.7 L) were run at mesophilic conditions (30-35 degrees C) in a temperature-controlled environment with three hydraulic retention times (theta) of 15.7, 12 and 8.0 days. Imposed volumetric organic loading rates (L-V) ranged from 0.65 to 4.257 kg COD/(m(3) day). The pH of the feed varied between 6.68 and 7.82. The hydraulic loading rates (L-H) were controlled between 0.105 and 0.21 m(3)/(m(2) day). The daily biogas production rates ranged between 4.2 and 29.4 L/day. High volumetric COD removal rates (R-V) ranging from 0.546 to 3.779 kg CODremoved/(m(3) day) were achieved. On the basis of experimental results, two empirical models having a satisfactory correlation coefficient of about 0.9954 and 0.9416 were developed to predict daily biogas production (Q(g)) and effluent COD concentration (S-e), respectively. Findings of this modeling study showed that optimal COD removals ranging from 86.3% to 90.6% were predicted with HRTs of 7.9, 9.5, 11.2, 12.6, 13.7 and 14.3 days, and L-V of 1.27, 1.58, 1.78, 1.99, 2.20 and 2.45 kg COD/(m(3) day) for the corresponding influent substrate concentrations (S-i) of 10,000, 15,000, 20,000, 25,000, 30,000 and 35,000 mg/L, respectively. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: poultry manure wastewater; COD removal; biogas production; modeling; nonlinear regression; ANAEROBIC-DIGESTION; TEMPERATURE; Engineering; Environmental Sciences & Ecology